A resource-based analysis of strategic alliances between knowledge intermediaries in regional innovation and entrepreneurial ecosystems - Philipp Bäumle; Kilian Bizer (Volkswirtschaftliches Institut für Mittelstand und Handwerk an der Universität Göttingen (ifh), 2022)
Notwithstanding a recent upsurge in interest in knowledge intermediaries and their roles in innovation and entrepreneurial ecosystems, we know little about the interplay between the activities of academia driven intermediaries and their publicly financed counterparts. Building upon a combination of principles derived from the resource based theory and the entrepreneurial ecosystems literature, this paper investigates the potentials of cooperation between different knowledge intermediaries. Therefore, we analyze the alignment of financial, knowledge, market and network resources in politically funded regional alliances between university internal and university external intermediaries by the means of a qualitative approach. We find that while knowledge intermediaries can benefit from access to additional ecosystem specific resources, the urge to improve the own position within the ecosystem hampers the will for cooperation and can lead to non performing resource alignments. This paper contributes to current scholarly discussions by suggesting and testing a theoretical foundation for analyzing the cooperative behavior of knowledge intermediaries in innovation and entrepreneurial ecosystems.
Keywords: I29; O31; O39; 330; resource-based view; strategic alliances; knowledge intermediaries; innovation and entrepreneurial ecosystems; qualitative case study